Beyond Patents: Assessing the Value and Impact of Research Investments: Proceedings of a Workshop–in Brief - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2017)
Companies know exactly what they spend on research, but knowing exactly what they get for their money is a more difficult question to answer. Without a good way to measure value, research can be viewed as a cost that can be cut to boost near-term earnings. The number of patents is one metric for measuring the value of research, but that information is not necessarily useful without knowing the business value of those patents in the marketplace. What other metrics serve to highlight the value of research and innovation? On June 27 and 28, 2017, the Government-University-Industry Research Roundtable held a meeting to explore these issues. This publication briefly summarizes the presentations and discussions from the meeting.
Keywords: Engineering and Technology; Policy for Science and Technology

Demographic Effects of Girls' Education in Developing Countries: Proceedings of a Workshop–in Brief - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2017)
Educating girls is a universally accepted strategy for improving lives and advancing development. Girls’ schooling is associated with many demographic outcomes, including later age at marriage or union formation, lower fertility, and better child health. However, the causal pathways between education and demographic outcomes are not well understood. To advance understanding of the relationships between girls’ education and demographic outcomes and to encourage more research on the determinants, content, context, and consequences of girls’ education the National Academies of Sciences, Engineering, and Medicine conducted a workshop addressing these issues on May 11 and 12, 2017. This publication briefly summarizes the presentations and discussions from the workshop.
Keywords: Education; Behavioral and Social Sciences

Strategies to Limit Sugar-Sweetened Beverage Consumption in Young Children: Proceedings of a Workshop—in Brief - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2017)
On June 21–22, 2017, the National Academies of Sciences, Engineering, and Medicine’s Food and Nutrition Board convened a workshop in Washington, DC, to explore the range of policies and programs that exist at the federal, state, tribal, and local levels to limit sugar-sweetened beverage consumption in children birth to 5 years of age. Topics examined over the course of the 1.5-day workshop included prevalence and trends in beverage intake among young children; beverage intake guidelines applicable to the age range of interest; challenges and opportunities of influencing beverage consumption; the role of industry in beverage intake; and knowledge gaps and research needs. This publication highlights key points made by individual speakers during the presentations and discussions.
Keywords: Food and Nutrition; Health and Medicine

Advancing Obesity Solutions Through Investments in the Built Environment: Proceedings of a Workshop—in Brief - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2017)
The built environment—the physical world made up of the homes, buildings, streets, and infrastructure within which we all live, work, and play—underwent changes during the 20th and 21st centuries. These changes contributed to a sharp decline in physical activity and affected access to healthy foods, which added to the weight gain observed among Americans in recent decades. As such, policies and practices that affect the built environment could affect obesity rates in the United States and improve the health of Americans. On September 12, 2017, the Roundtable on Obesity Solutions held a workshop to examine how investments in the built environment contribute to the prevention and treatment of obesity and the overall health of communities. Specifically, presenters discussed successful multisector strategies that encourage physical activity and improve diet, equity, environmental justice, and overall community health and well-being, as well as discussed approaches for scaling up and institutionalizing these strategies to advance obesity solutions. This publication briefly summarizes the presentations and discussions from the workshop.
Keywords: Food and Nutrition; Health and Medicine

Research and Technology Coordinating Committee Letter Report: March 28, 2017 - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2017)
A March 28, 2017 report from TRB's Research and Technology Coordinating Committee (RTCC) to the U.S. Federal Highway Administration (FHWA) offers recommendations addressing the barriers to deploying private-sector innovations and technologies; the evaluation of demonstration programs deploying technologies and pilot testing user-fee financing mechanisms; the completion of case studies of FHWA's research and technology program; and planning for a research and technology program to address the major challenges facing highway transportation for Congress's next transportation authorization.The RTCC’s charge is to monitor and review FHWA’s research and technology activities; advise FHWA on setting a research agenda and coordination of highway research with states, universities, and other partners; review strategies to accelerate the deployment and adoption of innovation; and identify areas where research may be needed. RTCC’s review includes the process of research agenda setting; stakeholder involvement; and the conduct of research, peer review, and deployment. The committee’s role is to provide strategic, policy-level advice on topical priorities, processes, and strategies to accelerate the adoption of innovation.
Keywords: Transportation and Infrastructure

Preparing for a Rapid Response to Major Marine Oil Spills: Protecting and Assessing the Health and Well-Being of Communities: Proceedings of a Workshop—in Brief - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2017)
On August 2–3, 2017, the National Academies of Sciences, Engineering, and Medicine held a workshop titled Preparing for a Rapid Response to Major Offshore Oil Spills: A Workshop on Research Needs to Protect the Health and Well-Being of Communities. Its objectives were to explore research needs and other opportunities for improving public health preparedness, response, and protection related to oil spills; consider how to work within and how to complement the existing oil spill response framework to improve the protection of community health and well-being; to inform discussions about how the Gulf Research Program and other divisions of the National Academies can support these efforts; and to foster connections among public health, oil spill practitioners, disaster research communities, and leaders from communities affected by oil spills. This publication briefly summarizes the presentations and discussions from the workshop.
Keywords: Health and Medicine; Conflict and Security Issues

Uses of Social Media to Inform Operational Response and Recovery During an Airport Emergency - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2017)
TRB's Airport Cooperative Research Program (ACRP) Synthesis 82: Uses of Social Media to Inform Operational Response and Recovery During an Airport Emergency summarizes airport practices and tools used by airport emergency managers. Using social media for emergency management, airports glean information and intelligence from the stream of posts and messages passing through social media and then apply this information to enhance situational awareness and resource allocation decisions by emergency managers. Such uses raise the stakes for timeliness of data extraction and validation of the results, especially if the information is going to be used for resource allocation and other decision making.
Keywords: Transportation and Infrastructure

Impacts of Laws and Regulations on CV and AV Technology Introduction in Transit Operations - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2017)
TRB's National Cooperative Highway Research Program (NCHRP) Web-Only Document 239: Impacts of Laws and Regulations on CV and AV Technology Introduction in Transit Operations explores the potential barriers imposed by operating policies, agency regulations, and governmental laws relative to the transit environment. Without adjustment, the combination of new technology with old rules could result in delays and restrictions to deployment, which may reduce the cumulative societal benefits of automated systems technology. This project presents a roadmap of activities to be performed by industry groups, legislatures, the federal government and others to facilitate automated roadway transit operations.
Keywords: Transportation and Infrastructure

Developing a Method Selection Tool for Travel Forecasting - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2017)
TRB's National Cooperative Highway Research Program (NCHRP) Web-Only Document 234: Developing a Method Selection Tool for Travel Forecasting documents research undertaken to provide guidance on travel forecasting methods to agencies with diverse planning needs. This project sought to produce applicable methods by evaluating agencies’ planning programs, desired performance metrics, requirements, and constraints, and this report documents the research and methods behind the final project and software tool.NCHRP Research Report 852: Method Selection for Travel Forecasting presents guidelines and a tool for travel-forecasting practitioners to assess the suitability and limitations of their travel-forecasting methods and techniques to address specific policy and planning questions.
Keywords: Transportation and Infrastructure

Enhancing Airport Wayfinding for Aging Travelers and Persons with Disabilities - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2017)
TRB's Airport Cooperative Research Program (ACRP) Research Report 177: Enhancing Airport Wayfinding for Aging Travelers and Persons with Disabilities provides guidance to assist aging travelers and persons with disabilities to travel independently within airports using pedestrian wayfinding systems. The guidebook addresses travel by people with cognitive, sensory, and other mobility challenges.The Wayfinding Accessibility Audit Checklist documents issues that should be considered in a baseline airport wayfinding accessibility audit; it is provided in Word format so that users can check items off the list. The research team collected ratings of airport wayfinding applications from users of those applications on the Application Review Criteria testing and comment form. A PowerPoint presentation provides an overview of the ACRP research produced as a part of this report.Disclaimer - This software is offered as is, without warranty or promise of support of any kind either expressed or implied. Under no circumstance will the National Academy of Sciences, Engineering, and Medicine or the Transportation Research Board (collectively "TRB") be liable for any loss or damage caused by the installation or operation of this product. TRB makes no representation or warranty of any kind, expressed or implied, in fact or in law, including without limitation, the warranty of merchantability or the warranty of fitness for a particular purpose, and shall not in any case be liable for any consequential or special damages.
Keywords: Transportation and Infrastructure

Overview of Airport Duties and Standards of Care in Airfield Accident Cases - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2017)
TRB's Airport Cooperative Research Program (ACRP) Legal Research Digest 33: Overview of Airport Duties and Standards of Care in Airfield Accident Cases provides an overview of the legal duties and standards of care that may create liability when operating a public airfield. It discusses negligence principles and reviews duties and standards of care in an airfield accident context, including the extent to which federal preemption may apply. The digest concludes with a section discussing many types of airfield conditions that have allegedly contributed to an accident or to liability concerns in past cases.
Keywords: Transportation and Infrastructure

Guidebook for Considering Life-Cycle Costs in Airport Asset Procurement - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2017)
TRB's Airport Cooperative Research Program (ACRP) Research Report 172: Guidebook for Considering Life-Cycle Costs in Airport Asset Procurement explores how other industries use the total cost of ownership (TCO) approach for initial procurement, and how to integrate this into future airport procurement practices. ATCO Tooland fiveinstructional videoson how to use the TCO Tool accompany the report.Airports, as well as other governmental entities, usually are required to take the lowest bid when procuring assets. This approach tends not to take into consideration the life-cycle costs, such as the operation and maintenance (O&M) costs, which can result in higher than anticipated costs from the O&M budget. Since the purchase of assets is allocated from capital funds that are managed by a person typically different than the person responsible for the day-to-day management of O&M funds, there can be a disconnect on what is considered “better” when considering two bids. Taking a life-cycle, also known as a TCO approach, to the initial procurement may ensure a more fiscally responsible use of funds.Disclaimer - This software is offered as is, without warranty or promise of support of any kind either expressed or implied. Under no circumstance will the National Academy of Sciences, Engineering, and Medicine or the Transportation Research Board (collectively "TRB") be liable for any loss or damage caused by the installation or operation of this product. TRB makes no representation or warranty of any kind, expressed or implied, in fact or in law, including without limitation, the warranty of merchantability or the warranty of fitness for a particular purpose, and shall not in any case be liable for any consequential or special damages.
Keywords: Transportation and Infrastructure

Challenges in Machine Generation of Analytic Products from Multi-Source Data: Proceedings of a Workshop - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2017)
The Intelligence Community Studies Board of the National Academies of Sciences, Engineering, and Medicine convened a workshop on August 9-10, 2017 to examine challenges in machine generation of analytic products from multi-source data. Workshop speakers and participants discussed research challenges related to machine-based methods for generating analytic products and for automating the evaluation of these products, with special attention to learning from small data, using multi-source data, adversarial learning, and understanding the human-machine relationship. This publication summarizes the presentations and discussions from the workshop.
Keywords: Math, Chemistry, and Physics; Surveys and Statistics

Synthesis of Information Related to Airport Practices: 2017 - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2017)
TRB’s Airport Cooperative Research Program (ACRP) Research Results Digest 26: Synthesis of Information Related to Airport Practices is a digest of the progress and status of ACRP Project 11-03, Synthesis of Information Related to Airport Practices.
Keywords: Transportation and Infrastructure

A Review of the Department of Transportation's Plan for Analyzing and Testing Electronically Controlled Pneumatic Brakes Letter Report (Phase 2) - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2017)
TRB's Committee on the Review of the Department of Transportation's (DOT) Testing of Electronically Controlled Pneumatic (ECP) Brakes has issued its final letter report. In response to a Congressional request, the committee reviews the conduct of DOT's tests, reports of test results, and analysis comparing the performance of ECP brakes relative to other braking technologies in reducing the incidence and severity of spills of crude oil or ethanol from derailments. The committee's report reviewing DOT's test and analysis plan, issued in February 2017, recommends that DOT test the timing of brake propagation for alternative systems, conduct statistical analyses of the multiple factors contributing to derailments, and extend its validation of its modeling and simulation approaches for comparing ECP brakes to other brake systems. The committee’s letter report reviewing the results of DOT’s testing and analysis, issued in September 2017, finds that DOT’s efforts to validate its model and simulation approaches are incomplete and unconvincing. Based on the results of testing and analysis provided by DOT, the committee is unable to make a conclusive statement about the emergency performance of ECP brakes relative to other braking systems.
Keywords: Transportation and Infrastructure

America's Future in Civil Space: Proceedings of a Workshop–in Brief - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2017)
Since the National Research Council released the report America’s Future in Space: Aligning the Civil Space Program with National Needs in 2009, numerous changes have occurred in the civil space arena. In May 2017, the National Academies of Sciences, Engineering, and Medicine convened a workshop on America’s Future in Civil Space with several objectives, including reviewing the history of U.S. space policy and how it might form a broad policy basis for twenty-first century leadership in space, examining the balance and interfaces between fundamental scientific research in space, human space exploration, robotic exploration, earth observations, and applications of space technology and civil space systems for societal benefits, and discussing the value, purpose, and goals of international cooperation in space. The workshop participants sought to capture what has changed, determine how to harness new opportunities, and decisively inform and encourage bold and timely implementation. This publication briefly summarizes the presentations and discussions from the workshop.
Keywords: Space and Aeronautics

Returns to Federal Investments in the Innovation System: Proceedings of a Workshop–in Brief - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2017)
Through grants, contracts, and loans, the federal government invests over $140 billion annually in research and development. Most economists agree that public support for research and development is essential given that the private sector—unable to internalize the social benefits—will underinvest in the creation of knowledge that may lead to innovation. Critics have questioned the adequacy of the return on this public investment, arguing that government investment is ineffective, inefficient, and may simply crowd out private investment. Overlaying these issues are questions about the broader impacts of these federal investments on inequality—that is, the distribution of gains from the fruits of innovation. On December 15, 2016, the Innovation Policy Forum of the Board on Science, Technology, and Economic Policy held a workshop designed to gather leading researchers to explore the returns to federal investments in the innovation system, which include economic growth, job creation, as well as improved health and quality of life. The workshop was structured into four panels investigating social returns to: (1) federal investments in basic research; (2) federal support to private-sector innovation (which include research and expenditure (R&E) tax credits, small business support, prizes, and the patent system, among other policies); (3) public investments in human capital and supporting infrastructure such as digital infrastructure; and (4) the relationship between innovation, inequality, and social mobility. This publication briefly summarizes the presentations and discussions from the workshop.
Keywords: Policy for Science and Technology

Airport Passenger Screening Using Millimeter Wave Machines: Compliance with Guidelines - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2017)
The Transportation Security Administration requested a study by the National Research Council (NRC) to establish the Committee on Airport Passenger Screening: Millimeter Wave Machines to evaluate two models of active millimeter wave scanners: the L3 ProVision 1 and L3 ProVision 2. Airport Passenger Screening Using Millimeter Wave Machines provides findings and recommendations on compliance with applicable health and safety guidelines and appropriateness of system design and procedures for preventing over exposure. This study addresses the issue of whether millimeter wave machines used at airports comply with existing guidelines and whether it would be possible for anything to go wrong with the machines so that, by mistake, it exposes a person to more than 10 W/m2.
Keywords: Engineering and Technology; Transportation and Infrastructure

Consequences of Delayed Maintenance of Highway Assets - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2017)
TRB's National Cooperative Highway Research Program (NCHRP) Research Report 859: Consequences of Delayed Maintenance of Highway Assets presents a process for quantifying the consequences of delayed maintenance of highway assets that considers the asset preservation policy, the maintenance and budget needs, and the analyses of delayed maintenance scenarios. This process considers delayed maintenance caused by the inability to meet the agency-defined application schedule or the unavailability of the funds required to perform all needed maintenance, and expresses the consequences in terms of asset condition and the costs to owners and road users. Detailed descriptions of the use of the proposed process to quantify the consequences of delayed maintenance for seven highway assets are available in appendices from the contractor’s final report:Appendix C-PavementsAppendix D-BridgesAppendix E-CulvertsAppendix F-GuardrailsAppendix G-LightingAppendix H-Pavement markingsAppendix I-Signs
Keywords: Transportation and Infrastructure

Views of the U.S. National Academies of Sciences, Engineering, and Medicine on Agenda Items of Interest to the Science Services at the World Radiocommunication Conference 2019 - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2017)
The radio frequency spectrum is a limited resource with ever increasing demand from an expansive range of applications—all the way from commercial, such as mobile phones, to scientific, such as hurricane monitoring from space. Since radio waves do not stop at national borders, international regulation is necessary to ensure effective use of the radio spectrum for all parties. Every 2 to 5 years, the International Telecommunication Union convenes a World Radiocommunication Conference (WRC) to review and revise the international radio regulations. This report provides guidance to U.S. spectrum managers and policymakers as they prepare for the WRC in 2019. While the resulting document is targeted primarily at U.S. agencies dealing with radio spectrum issues, other Administrations and foreign scientific users may find its recommendations useful in their own WRC planning.
Keywords: Space and Aeronautics